Cellular and Molecular Mechanisms of Immuno-modulation by Ganoderma lucidum - Zhi-Bin Lin (Elsevier, 2005)
Ganoderma lucidum (Leyss. ex Fr.) Karst. (Lingzhi or Reishi) has been used for a long time in China to prevent and treat various human diseases. G. lucidum polysaccharides extracted from G. lucidum are one of efficacious ingredient groups of G. lucidum. A number of reports have demonstrated that G. lucidum polysaccharides modulate immune function both in vivo and in vitro. The immuno-modulating effects of G. lucidum polysaccharides were extensive, including promoting the function of antigen-presenting cells, mononuclear phygocyte system, humoral immunity, and cellular immunity. Cellular and molecular mechanisms, possible receptors involved, and triggered signaling cascades have also been studied in vitro. However, whole animal experiments are still needed to further establish the mechanism of the immunomodulating effects by G. lucidum. Evidence-based clinical trials are also needed. Keywords:: Ganoderma lucidum, polysaccharide, immuno-modulation, mechanism